EFFECT OF DIETARY SUPPLEMENTATION OF VITAMIN E AND SELENIUM ON TOTAL ANTIOXIDANT STATUS AND IN VITRO IMMUNE COMPETENCE IN GROWER GHUNGROO PIGS - Rubayat Hussain; T. Samui; Joycy Seiba Khukhodziinai; P. K. Das; P. R.Ghosh; D. Banerjee; K Das; S. Naskar; S. Bag; J.Mukherjee (Exploratory Animal and Medical Research, 2024)
The current study aimed to assess the effects of dietary vitamin E and selenium supplementation on antioxidant status and in vitro immune competence in grower Ghungroo pigs. Eighteen healthy female Ghungroo pigs (Sus scroffa domestica) between the ages of two and three months were divided into three groups at random: the control group (n = 6) was fed only the basal diet, the treatment-1 (T1) group (n = 6) was fed the basal diet with vitamin E at a rate of 11 IU/kg feed, and the treatment-2 (T2) group (n = 6) was supplemented with selenium at a rate of 0.15 mg/kg feed every day, according to NRC recommendations. Blood samples were collected from all the experimental animals on days 15, 30, 45, and 60 of supplementation for analysis. Total antioxidant status was assessed using kits available commercially following the manufacturer's instructions. Colorimetric NBT and MTT assays were done to evaluate in vitro phagocytic activity and lymphocyte proliferation response respectively. This study is the first to evaluate the total antioxidant status and in vitro immune function of grower Ghungroo pigs. Both vitamin E and selenium supplementation increased overall antioxidant status, with vitamin E having a stronger effect than selenium. The vitamin E-treated group exhibited the highest lymphocyte proliferation response, followed by control and selenium-treated groups. Neutrophils from the vitamin E-treated pigs showed significantly (p<0.001) higher phagocytic activity compared to the control and selenium-treated groups. So, it can be concluded from the above findings that both vitamin E and selenium improved the body's overall antioxidant status and immune function by enhancing lymphocyte proliferation response and neutrophil phagocytic activity, with vitamin E showing a more pronounced effect than selenium.